Organizational Neuroscience: A Bibliometric Analysis and Systematic Literature Review - Nihan Tomris Küçün; Hazal Duman Alptekin (Istanbul Business Research)
The main objective of this paper is to examine the current state of the literature on organizational neuroscience. This study provides the most comprehensive overview of the development of organizational neuroscience which includes the last 13 years. It also presents how bibliometric and systematic review methodologies can be used together to explore emergent research areas. Bibliometric and systematic review methods were used to review studies carried out in the area of organizational neuroscience from 2007 to 2020. The articles were accessed through the Web of Science (WOS) database which was analyzed by using VOSviewer and SciMAT. Initially, 44 articles were determined to explain the intellectual structure of organizational neuroscience. Then, we conducted a systematic review in Scopus, WOS, and Google Scholar databases to determine which neuroscientific methodologies were prevalent in the scope of organizational neuroscience. As a result, a total of 42 studies adopting the empirical approach were identified. Evidence shows that the majority of the studies were conducted in the US and UK. The most commonly used techniques were electroencephalography (EEG) and functional magnetic resonance (fMRI). “Leadership” and “decision-making” studies were the most researched topic connected with organizational neuroscience. Although there has been a steady increase in the number of publications on organizational neuroscience in the last 20 years, empirical studies have a narrow scope in the literature.